An RNA interference/adeno-associated virus vector-based combinatorial gene therapy approach against Hepatitis E Virus - Zhang, Cindy; Freistaedter, Andrew; Schmelas, Carolin; Gunkel, Manuel; Dao Thi, Viet Loan; Grimm, Dirk (Hepatology communications, 2022)
Hepatitis E virus (HEV) is a major public health problem with limited therapeutic options. Here, we engineered adeno-associated viral vectors of serotype 6 (AAV6) to express short hairpin RNAs (shRNAs) against HEV transcripts with the prospect of down-regulating HEV replication in vivo. We designed 20 different shRNAs, targeting the genome of the HEV genotype 3 (GT3) Kernow-C1 p6 strain, for delivery upon AAV6 transduction. Using an original selectable HEV GT3 reporter replicon, we identified three shRNAs that efficiently down-regulated HEV replication. We further confirmed their inhibitory potency with full-length HEV infection. Seventy-two hours following transduction, HEV replication in both systems decreased by up to 95%. The three most potent inhibitory shRNAs identified were directed against the methyltransferase domain, the junction region between the open reading frames (ORFs), and the 3´ end of ORF2. Targeting all three regions by multiplexing the shRNAs further enhanced their inhibitory potency over a prolonged period of up to 21 days following transduction. Conclusion: Combining RNA interference and AAV vector-based gene therapy has great potential for suppressing HEV replication. Our strategy to target the viral RNA with multiplexed shRNAs should help to counteract viral escape through mutations. Considering the widely documented safety of AAV vector-based gene therapies, our approach is, in principle, amenable to clinical translation.